„Doorgaan en niet vergeten!“ Otto Schumacher (1908–1988). Communist, hulpverlener en verzetsman - Krutzen, Marcel (Historisch Cahier Parkstad Limburg, 2024)
Keywords: Aachen (Region); Antifaschismus; Flüchtlingshilfe; Heerlen; Kommunismus; Konzentrationslager; Politischer Gefangener; Soziale Situation; Steinkohlenbergbau; Widerstand

Zo dicht bij elkaar, maar toch heel anders. Eigendomsverhoudingen, productie en werkgelegenheid in de vier mijnbouwgebieden in het Maas-Rijngebied - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2016)
Keywords: Arbeitsmarkt; Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Changing Border Regimes. Mining, and Cross-border Labor in the Dutch–Belgian–German Borderlands, 1900–1973 - Knotter, Ad (Journal of Borderlands Studies, 2014)
„In this article the incidence of cross-border commuting to the mining districts in the Belgian–Dutch–German borderlands, known today as the Euregion Meuse-Rhine, will be related to the impact of state borders in different periods. Cross-border labor was closely related to changing border regimes based on uneven economic development, (un)familiarity, and the policy impact of powerful institutions like the state and the church. The main argument is that after the First World War in Dutch Limburg a conscious policy to control the labor force and bind them to mining in the region was relatively successful. Discrepancies in wages and employment opportunities led to border-crossing during restricted periods and for specific groups of workers only.“
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Mijnbouw en grensarbeid in het Nederlands-Belgisch-Duitse grensgebied, 1900–1973. Een overzicht - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2014)
Keywords: Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

The impact of boundaries on cross-border mobility and migration in the Liège-Limburg area (19th–20th centuries) as retrieved from population records - Rutten, Willibrord (Internationales Archivsymposion in Luxemburg (2012). Grenzüberschreitende Migration und Archive. Annalen, mit einem Nachtrag zum Symposion Lüttich (2011) Erster Weltkrieg, 2013)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Goed betaald? Mijnwerkerslonen en arbeidsmarkt in het Nederlands-Duits-Belgische grensgebied in de achttiende en negentiende eeuw - Gales, Ben A. (Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2008)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Secondary labour force of permanent staff? Foreign workers in the Aachen coal mines - Klank, Kristin (TSEG - The Low Countries Journal of Social and Economic History, 2008)
Abstract: „The paper gives an overview of the recruitment and professional status of workers in the coal mining district of Aachen from different origins, i.e. local miners, miners from other German coal districts, cross-border commuters from Dutch South-Limburg and labour migrants. Migration history generally assumes that foreign workers were primarily employed as temporary workers in workplaces abandoned by the local population. This article argues that the labour market situation of foreign commuters and labour immigrants has to be studied separately. Commuters were primarily skilled miners, who came to the mines on their own account. After the First World War, labour mobility between the Aachen region and South-Limburg was ephemeral and often resulted from sudden institutional changes. In general, long distance labour migrants were unskilled. They arrived in the mines in large groups hired directly by agents of the mines or mediated by the Federal Employment Office. The position of foreign immigrants underwent important changes. During the first recruitment drives of the Aachen mines between 1906 and 1912, immigrants were indeed considered as temporary workers; after the Second World War, the companies tried hard to make these workers stay beyond the minimal period of one year. Long-term labour contracts could lead to integration of immigrant workers into the permanent workforce, but also penalised workers who wished to leave prematurely.“
Keywords: Aachen (Region); Arbeitsmigration; Niederländer; Steinkohlenbergbau; Südlimburg (Niederlande)

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)